Lewis acid-catalyzed formal 1,3-hydroxy migration of arylvinyl carbinols - Amano, Koutarou; Kawasaki-Takasuka, Tomoko; Mori, Keiji (Synlett)
Although the 1,3-hydroxy migration reaction of arylvinyl carbinols is a valuable molecular transformation, examples of Lewis acid-catalyzed reactions remain quite limited. We found that the target Lewis acid-catalyzed reaction proceeded smoothly when acetone was used as the reaction medium. This catalytic system was applicable to arylvinyl carbinols having electron-deficient aromatic rings, a little-studied and challenging topic in 1,3-hydroxy migration chemistry.